Economic losses and poverty effects of droughts and floods in Malawi - Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2009)
Droughts and floods are a capricious part of life for many Malawians. The country depends heavily on rain-fed agriculture and so it is crucial that we understand the implications of these climate events. Not only are rural livelihoods affected, but urban households are also vulnerable to food shortages and rising prices. Finding ways to overcome the losses from droughts and floods is a policy imperative.